The Influence Of Competence And Internal Control System On Fraud In DPUTR Sumedang District - Alfirdaus, Muhammad Recky; Yuniawati, Ayi Srie; Utami, Anita Dwi (LPPM Universitas Sebelas April, 2025)
Fraud cases in the public sector are increasing and have an impact on state losses and decreased public trust in government institutions. This phenomenon also occurs in local government agencies, including in project and financial management at the agency. This study aims to analyze the effect of competence and internal control system on fraud, both partially and simultaneously, at the Public Works and Spatial Planning Office of Sumedang Regency. This research uses a quantitative approach with a survey method. Data was collected through a questionnaire of 40 respondents with a saturated sample technique. The results showed that competence has a significant effect on fraud that employees with high competence have the ability to understand and exploit the system if not accompanied by integrity, as well as the internal control system has a significant effect the findings indicate that even though the internal control system has been implemented, fraud still occurs due to weak implementation and supervision, this shows that an internal control system that is administrative in nature is not sufficient to prevent fraud. Simultaneously, both variables have an effect on fraud prevention. This finding shows that the combination of the two can create an environment that allows fraud to occur if the internal control system is weakly implemented.